Effects of comorbidity and medication use on the haemodynamic status during office‐based laryngeal procedures: A prospective cohort study. (29th June 2017) - Wang, C.T.; Liao, L.J.; Lo, W.C.; Huang, T.W.; Cheng, P.W.
Abstract : Objective: Office‐based laryngeal procedures (OBLPs) are emerging as effective alternative modalities for vocal disorders. This study systematically investigates the haemodynamic status of patients, specifically focusing on the potential effects of underlying comorbidity and medication use. Design: Prospective cohort study. Setting: Tertiary referral centre. Participants: We prospectively recruited 214 consecutive patients who received OBLPs during January‐December 2015. All procedures were performed under local anaesthesia without sedation, in an upright (sitting) position. Main outcome measures: We measured heart rate (HR), systolic and diastolic blood pressure, and oxygen saturations at baseline (before procedure), immediately after local anaesthesia to the pharynx and larynx, immediately after completing of procedure, and 20 minutes after the procedure. Results: Systolic, diastolic blood pressures and HR all significantly increased after local anaesthesia, and gradually decreased after the procedure ( P <.01). Oxygen concentration remained unchanged. Patients with comorbidity and those receiving vasoactive medications showed significantly higher perioperative blood pressures than the other patients ( P <.05), but the trend remained similar. Prominent hypertension (systolic ≥160 mm Hg or diastolic ≥100 mm Hg) was noted in 17 patients, more commonly in patients with older age, higher baseline blood pressures and receiving vasoactive medications. Only 2% of patients with normal baseline measurements developed prominent hypertension perioperatively. Tachycardia (HR≥100 bpm) developed in 22 patients, more frequently in patients with higher baseline HRs, and perceiving greater discomforts. Conclusion: This study revealed that routine haemodynamic monitoring may not be necessary for all the OBLPs, but should be considered for older patients, those with higher baseline blood pressure or HR, sensitive patients who might be more susceptible to perioperative discomfort, and those receiving vasoactive medications.